Effects of stimulation site and protocol on autonomic responses to auricular vagus nerve stimulation - Gharabaghi, Alireza; Keute, Marius (Frontiers in Neuroscience, 2025)
Transcutaneous auricular vagus nerve stimulation (taVNS) modulates autonomic function, but the influence of stimulation site and protocol remains unclear. In two within-subject experiments in young healthy participants (study 1: n = 15, study 2: n = 21), we examined how these parameters affect heart rate variability (HRV) as participants performed a visual detection task to stabilize arousal state while randomized stimulation blocks were applied. In study 1, burst (5 pulses at 25 Hz repeated every second), 1 Hz, and 25 Hz protocols were applied at the cymba conchae, with burst stimulation also delivered at the earlobe. In study 2, burst stimulation was applied at cymba conchae, fossa triangularis, tragus, and earlobe sites. While most HRV indices remained unchanged, stimulation-specific effects were observed for SDNN, a global marker of autonomic tone. Burst stimulation at both cymba conchae and earlobe sites produced notable SDNN changes, suggesting sensitivity of cardiac variability to stimulation protocols. These findings indicate that taVNS parameters modulate autonomic output and suggest that earlobe stimulation may evoke measurable autonomic responses under certain conditions. Further studies with larger samples and extended physiological and behavioral monitoring are warranted to confirm these conclusions.